The Impact of Triple Bottom Line Based CSR Program in the Local Community Food Processing Industry - Irawan, Enjang Pera (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The Company's involvement in continuously providing the additional value to the environment in which the Company operates is a necessity and a commitment that needs to be maintained. Thus, the Company can be a trusted partner for many parties, especially for the community and government in developing the environment and people.In line with this, the Company must encourage the realization ofquality of life ehancement, through the development of programs that support sustainable development including economic aspects, health, education, and environmental management, by involving the worker awareness, the local community, the government and large community.Based on these explanations, the researcher is interested in researching and focusing this research on the impact of triple bottom line-based CSR program in the local community food processing industry carried out by PT Energi Mega Persada Tbk. (EMP). This method used in this researchwas a qualitative method with a single case study design.The results of this research are expected to provide various recommendations related to the communication innovation, on how to implement the communication aspect in revealing the impact of triple bottom line-based CSR program in the local food processing industry. In addition, this research is expected to inspire and become a role model for companies that will implement triple bottom line-based CSR program for Sustainable Development. Academically, this research is expected to be a reference for the further research and can enrich the scientific field of communication, especially Public Relations, regarding to the discussion of CSR programs analysis.